REPRESENTASI CITRA KEPALA NEGARA DALAM VIDEO BLOG (VLOG) YOUTUBE PRESIDEN JOKO WIDODO “#JOKOWIMENJAWAB EPISODE 1” (Analisis Semiotika Roland Barthes) - Sarizalia Plantika Ginting; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Video Blog (vlog) President Joko Widodo in Youtube channel President Joko Widodo is one of Vlog which is quite famous in cyberspace. In Vlog President Joko Widodo there are some videos that are quite phenomenal among the people and one of them is Vlog #Jokowi Answer Episode 1. In the video, President Jokowi provides an opportunity for teenagers to record questions in various themes that will be answered directly by President Jokowi on video the. This study aims to determine the meaning of denotation, connotation, and myths and how the representation of the image of the head of the State displayed on the video. This research method using qualitative method with Roland Barthes semiotics analysis approach which consist of denotation mean, connotation meaning, and semiotics myth used to know the meaning of word and interaction. Technique Data collecting used is documentation study, observation study, literature study, data searching done online. The object to be analyzed is a blog video titled #JokowiMawab Episode 1. The results showed that there are three meanings according to Roland Barthes semiotics. The meaning of denotation is a literal meaning of dialogue, expression, and direct answer out of the mouth of President Joko Widodo. The meaning of connotation is the hidden messages about President Jokowi's love of rock and metal, his views on politics, the creative industry in Indonesia, and his views on Indonesian youth. While the myth contained obtained through ideas and understanding of teenagers around President Jokowi. The cira representation shown is President Jokowi as a positive person. Teurtama in spirit, forward thinking, community service, creative, and innovative.Keywords: semiotic, Image, Vlog